Comparison of the risk of noise-induced hearing loss between male police officers and male non-police officers: a nationwide cohort study using propensity score matching in South Korea - Woo-Ri Lee; Kyu-Tae Han; Ki-Bong Yoo; Jin-Ha Yoon (BMC, 2024)
Abstract Background Police officers are at a high risk of noise-induced hearing loss (NIHL) owing to the nature of their work. Therefore, this study aimed to compare the risk of NIHL in police officers and controls. Methods This study used the National Health Insurance claims data of workers aged 25-65 years obtained from 2005 to 2015. The case group comprised police officers, while the control group comprised general workers and public officers. The study followed a three-phase cohort design. The standardized incidence ratio (SIR) was calculated using an indirect standardization method based on age. Propensity score matching was performed using the greedy matching method, with a police officer-to-control group ratio of 1:3. Cox regression analysis was performed for each matched control group. Statistical significance was determined by a lower limit of greater than 1, based on the 95% confidence interval (CI). Results The SIR values for police officers were 1.62 (95% CI: 1.44-1.82) compared with general workers and 1.78 (95% CI: 1.66-1.73) compared with public officers. Police officers exhibited an increased risk of NIHL compared with general workers (hazard ratio (HR): 1.71, 95% CI: 1.49-1.98) and public officers (HR: 2.19, 95% CI: 1.88-2.56). Conclusions It is necessary to prevent NIHL by reducing occupational noise exposure through measures such as wearing earplugs, improving shooting training methods, and improving the shift work system.